PROTEIN DEGRADABILITY OF GRASSLAND FORAGE UNDER SIMULATED ROTATIONAL SPRING GRAZING - Stojanović, Bojan D.; Aleksandar, Simić S.; Grubić, Goran A.; Đorđević, Nenad Ž.; Božičković, Aleksa Đ.; Davidović, Vesna M. (Journal of Agricultural Sciences (Belgrade), 2019)
A cutting experiment was conducted to analyze the changes in crude protein (CP) fractions content and in estimated ruminal protein degradability of forage, obtained in conditions of simulated rotational spring grazing on permanent grassland. The field trial was conducted on permanent pasture during 2015 included three cuttings as a simulated rotational spring grazing. For determination of protein degradability of pasture forage, the fractionation of CP according to Cornell Net Carbohydrate and Protein System (CNCPS v6.5) and the Streptomyces griseus protease assay were used. Relative to CP, there were not found significant differences between cuts for ammonia N content (A1 fraction) and for protein fraction C which is completely unavailable to the animals. Values for soluble true protein (fraction A2) and cell wall associated protein which is acid detergent soluble (B2) were significantly increased (p